Analysis of The Prevention Needs of Adolescent Girls' Mental Health Disorders: A Qualitative Study - Choirunissa, Risza; Nugraheni, Sri Achadi; Purnami, Cahya Tri; Wahyuningsih, Nur Endah (JURNAL INFO KESEHATAN, 2024)
Adolescent girls in Jakarta face unique mental health challenges due to cultural, social, and environmental factors. Understanding their prevention needs is critical to inform targeted interventions. This qualitative study aimed to explore the prevention needs of mental health disorders among adolescent girls in Jakarta, shedding light on their experiences and requirements for effective support. We conducted a qualitative study in Jakarta, Indonesia. Participants included 4 counseling guidance teachers consisting of public schools, private schools, Islamic and Christian affiliated schools, 2 parents, 1 coordinator of the School Health Unit, 2 health workers who hold PKPR projects, and the supervisor in charge of the school health unit, selected through purposive sampling. Data were collected through focus group discussion and analyzed using thematic analysis manually. The study reveals that teachers and parents have varying levels of exposure to adolescent mental health information, with some offering counseling but not always tailored to girls' needs. Parents often rely on subtle cues to detect mental health issues in their daughters. There's room for improvement in addressing girls' mental health needs in schools, with specific training for teachers and more open parent-daughter communication. Further research is needed to ensure uniform support for adolescent mental health.